PENGARUH SELF-EFFICACY DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN PAMULANG KOTA TANGERANG SELATAN - Ade Maulana Saputra; Maghfiroh Yanuarti (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
Abstract.  This study aims to analyze the effect of Self-Efficacy (X1) and Work Discipline (X2) on Employee Performance (Y) at the Pamulang District Office, South Tangerang City. The research uses a quantitative approach with a cross-sectional design. Data were collected through a Likert-scale questionnaire distributed to 88 employee respondents. Data analysis techniques include classical assumption tests, partial simple linear regression, multiple linear regression, correlation coefficient (r), and coefficient of determination (R²) using SPSS version 25.Partial regression test results prove that Self-Efficacy has a positive and significant effect on performance (t = 5.455; Sig. = 0.000 < 0.05), and Work Discipline also has a positive and significant effect on performance (t = 2.777; Sig. = 0.007 < 0.05). Simultaneously, both independent variables have a significant effect on Employee Performance (F = 37.571; Sig. = 0.000 < 0.05) with R = 0.685 and R² = 0.469, indicating that 46.9% of performance variation can be explained by Self-Efficacy and Work Discipline, while 53.1% is influenced by other factors outside the model. The regression model is declared free from multicollinearity (VIF = 1.400) and heteroskedasticity (Glejser Sig. X1 = 0.089; X2 = 0.957 > 0.05). The study concludes that strengthening employee belief in personal capability (Self-Efficacy) and consistent enforcement of work discipline significantly improve employee performance at the Pamulang District Office. Leadership support and rule-based disciplinary supervision are recommended to reinforce organizational performance. Abstract.  This study aims to analyze the effect of Self-Efficacy (X1) and Work Discipline (X2) on Employee Performance (Y) at the Pamulang District Office, South Tangerang City. The research uses a quantitative approach with a cross-sectional design. Data were collected through a Likert-scale questionnaire distributed to 88 employee respondents. Data analysis techniques include classical assumption tests, partial simple linear regression, multiple linear regression, correlation coefficient (r), and coefficient of determination (R²) using SPSS version 25.Partial regression test results prove that Self-Efficacy has a positive and significant effect on performance (t = 5.455; Sig. = 0.000 < 0.05), and Work Discipline also has a positive and significant effect on performance (t = 2.777; Sig. = 0.007 < 0.05). Simultaneously, both independent variables have a significant effect on Employee Performance (F = 37.571; Sig. = 0.000 < 0.05) with R = 0.685 and R² = 0.469, indicating that 46.9% of performance variation can be explained by Self-Efficacy and Work Discipline, while 53.1% is influenced by other factors outside the model. The regression model is declared free from multicollinearity (VIF = 1.400) and heteroskedasticity (Glejser Sig. X1 = 0.089; X2 = 0.957 > 0.05). The study concludes that strengthening employee belief in personal capability (Self-Efficacy) and consistent enforcement of work discipline significantly improve employee performance at the Pamulang District Office. Leadership support and rule-based disciplinary supervision are recommended to reinforce organizational performance.